Difficulties and challenges facing open educational resources - Al-Mismari, Abdel Fattah Abdel Rahim Jibril Muhammad (Tobruk University Journal of Social and Human Sciences, 2020)
The paper is contains on sum of the mean  points related to the difficulties and the challenges which facing the open educational resources and its impact on its future in the developing countries , it takes logical steps to views this stages. at the beginning concentrate on the concepts of open educational resources generally, its difficultie,managerial , academictechnologic , which it facing the open education and make the students are; suffering from the education problems In addition , identify the concepts of open educational resources , finally view the challenges which facing this programs of open educational; in this countries to change the quality of the education until transform it to be able to achieve progress the educational system;